PEMANFAATAN AIR PANAS BUMI UNTUK ALAT PENGERING GABAH DI BUKIT KASIH KANONANG - Glendi Umbas; Frans Palobo Sappu; Tertius V Y Ulaan (JURNAL POROS TEKNIK MESIN UNSRAT, 2014)
Traditionaly heat from the sun is employ in drying. The weakness is drying time relatively too long and weather can not be controlled. The utilization of spring water in Bukit Kasih Kanonang for drying of grain is an alternative that does not depend on weather conditions. The spring water heats the plate, then hot of plate directly in contact with the grain. It is causes the grain receiving heat and evaporate the water in the grain, them the grain dried well. From this research, it can be concluded that the drying time effect on grain’s moisture content linearly. The longer the drying time, the lower the moisture content of grain. In this research, the process of drying grain with water temperature 60 0C is enough dry the grain as 2, 104 kg during 5.13 hours. Keywords : Grain, Spring Water, Bukit Kasih Kanonang